Comparative effectiveness and safety of nab-paclitaxel plus carboplatin vs gemcitabine plus carboplatin in first-line treatment of advanced squamous cell non-small cell lung cancer in a US community oncology setting - Mudad R (Dove Medical Press, 2017)
Raja Mudad,1 Manish B Patel,2 Sandra Margunato-Debay,2 David Garofalo,3 Lincy S Lal4 1University of Miami Miller School of Medicine, Sylvester Comprehensive Cancer Center, Hollywood, FL, USA; 2Celgene Corporation, Summit, NJ, USA; 3Cardinal Health, Dallas, TX, USA; 4University of Texas School of Public Health, Houston, TX, USA Introduction: Real-world comparative effectiveness, safety, and supportive care use of nab-paclitaxel plus carboplatin vs gemcitabine plus platinum were analyzed in patients with advanced or metastatic squamous cell non-small cell lung cancer (NSCLC).Materials and methods: Patients who received ≥ 1 cycle of first-line nab-paclitaxel plus carboplatin or gemcitabine plus platinum were identified from the Navigating Cancer database. Clinical effectiveness endpoints included overall survival (OS) and time to treatment discontinuation (TTD). Other endpoints included safety and utilization of supportive care. Cox proportional hazards models were used to control for potential confounding effects of baseline characteristics.Results: In total, 193 patients were included (nab-paclitaxel plus carboplatin, n = 61; gemcitabine plus platinum, n = 132). Baseline characteristics were generally similar between the cohorts. Patients receiving nab-paclitaxel plus carboplatin had a significantly longer OS than those receiving gemcitabine plus carboplatin (median, 12.8 vs 9.0 months; P = 0.03). However, the adjusted difference was not statistically significant (adjusted HR 1.55; 95% CI, 0.99–2.42; P = 0.06). nab-Paclitaxel plus carboplatin-treated patients had significantly longer TTD than gemcitabine plus carboplatin-treated patients (median, 4.3 vs 3.5 months; P = 0.03; adjusted HR 1.39; 95% CI, 1.01–1.90; P = 0.04). Grade 3 or 4 anemia and neutropenia were significantly lower in patients treated with nab-paclitaxel plus carboplatin vs gemcitabine plus carboplatin. Nausea and neuropathy (grade not specified) were significantly higher in the nab-paclitaxel plus carboplatin than the gemcitabine plus carboplatin group. No differences in supportive care use were observed between the cohorts.Conclusion: These real-world data support the effectiveness and safety of nab-paclitaxel plus carboplatin for first-line treatment of advanced squamous cell NSCLC. Keywords: chemotherapy, doublet treatment options, electronic medical records, NSCLC, real-world evidence, retrospective analysis